Human rights: a challenge to critical social work practice and education - Nipperess, Sharlene (Curtin University, 2013)
This qualitative research explores how Australian social workers position human rights in practice and education and the implications of this for critical social work. It focuses on the experiences of social work practitioners working with refugees and asylum seekers and social work academics in Australian universities. The central thesis is that the concept of human rights, though highly contested and problematic, can make an important contribution to critical social work practice and social work education.